Some necessary and sufficient conditions for the output controllability of temporal Boolean control networks. (6th February 2014) - Liu, Yang; Lu, Jianquan; Wu, Bo
Abstract : This paper investigates the output controllability problem of temporal Boolean networks with inputs (control nodes) and outputs (controlled nodes). A temporal Boolean network is a logical dynamic system describing cellular networks with time delays. Using semi-tensor product of matrices, the temporal Boolean networks can be converted into discrete time linear dynamic systems. Some necessary and sufficient conditions on the output controllability via two kinds of inputs are obtained by providing corresponding reachable sets. Two examples are given to illustrate the obtained results.